Serum D-dimer is not predictive of placenta-mediated complications in pregnancy at high risk: The multicentric prospective cohort AngioPred study - Agathe Hovine; Céline Chauleur; Céline Chauleur; Christophe Gauld; Florence Rancon; Florence Rancon; Jean-Christophe Gris; Jean-Christophe Gris; Jean-Christophe Gris; Brigitte Tardy; Antoine Giraud; Antoine Giraud; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: The theory that D-dimer level might has a predictive or diagnostic role in preeclampsia needs to be explored. Aim of the study was to evaluate the association between serum D-dimer level and the occurrence of placenta-mediated complications (PMC) in a pregnant population at high risk.Methods: A prospective multicenter cohort study including 200 pregnant women was conducted.Results: Serum D-dimer increases throughout pregnancy, with the highest levels at the end of gestation. Serum D-dimer level was similar for women with PMC and with no complication. Serum D-dimer level was not different in women with preeclampsia versus uncomplicated women. Serum D-dimer level was not different in women with early or late preeclampsia versus uncomplicated women.Conclusion: This result suggests that serum D-dimer level was not predictive of the PMC occurrence. This corroborates the fact that the origin of PMC based more on immunity than in hemostasis.